A trajetória histórica da Escola de Enfermagem da Universidade Federal de Minas Gerais: desdobramentos da Federalização 1950-2004 - Fernanda Batista Oliveira Santos (2018)
This research was intended to analyze the historical trajectory of the School of Nursing of the Federal University of Minas Gerais, focusing on its federalization. The initial milestone (1950) corresponds to the year of the attachment of School of Nursing of the Federal University ofMinas Gerais to the Faculty of Medicine, federalized as an academic unit of the Federal University of Minas Gerais through Federal Law 775/1949. The final milestone (2004) was selected due to the fact of being a year of significant changes, such as the approval of the Doctoral degree and the establishment of the Nutrition undergraduate course. Starting from theassumption that the School of Nursing takes on a process of growing secularisation and that the provision both of these courses is seen as the closing of a cycle that consolidates the idea of the School as an autonomous academic unit of a Federal University that has strengths in the training of researchers and that integrates several areas of knowledge in the same locus of production of scientific knowledge. The chosen method was the historical-documentary with the use ofwritten and oral sources. The analysis was supported on Eliot Freidson (1996), as understood that during the study of the School Carlos Chagas / School of Nursing of the Federal University of Minas Gerais, a process of independence of the School was unveiled and the paths of theprofessionalization of nursing in the Minas Gerais. The School of Nursing's eighteen first years inside the Federal University of Minas Gerais structure has the milestones the School annexation process and the later disengagement from the Faculty of Medicine during theUniversity Reform (1968). This phase is marked by a management of sister nurses of charity and administrative and financial subordination to Faculty of Medicine, besides the lack of chair in the University Council. Although it was an express desire from the lay nurses teachers ofCarlos Chagas School to break up from the Faculty of Medicine subordination, the break up was possible only with the 1968 Reform. From 1967, School of Nursing of the Federal University of Minas Gerais is reassumed by the lay nurses, but the decades of 1970 and 1980,marked by the military dictatorship and the process of political re-democratization of the country, unveil the nurses learning in the field of university management. Accordingly, the specialization courses and extensionist joints directed to the health care marked the initiativesof this period. In 1993, teachers who broke with the extensionist and care-centered profile managed to approve the masters degree course, who sought qualification beyond the borders of School of Nursing of the Federal University of Minas Gerais. The doctoral degree and theNutrition undergraduate course, started in 2004, enabled the School to integrate the ideals of a federal university, thus producing researches, qualifying the teaching staff of the institution, expanding physical space and the interface possibilities between the health knowledge and theSchool's dialogue with the healthcare system. The perception of the need for expanding the School was significantly influenced by its integration with research promotion networks such as the Kellogg Foundation; the Nursing Development Program; the Project of Professionalization of Nursing Workers; Assistance Teacher Integration, UNI and REDEUNIDA projects. The conclusion is that the nursing is a success case in the perspective of State investment in public healthcare and that the School of Nursing of the Federal University of Minas Gerais incorporated professional status and has been reconfiguring itself as long thelaicinization was embraced, securing as reference in the human resources formation for nursing, outlining the nursing professionalization trends in the Minas Gerais state, reverberating the scenarios of Brazilian nursing and Latin America and the Unified Health System.